Pengembangan Buku Ajar Fisika Berbasis Kotekstual pada Materi Medan Magnetik Siswa Kelas XII SMA Negeri 2 Muara Beliti - Dela Aryansi; Yaspin Yolanda (LP4MK STKIP PGRI Lubuklinggau, 2020)
This research aims to develop a textbook of physics based on contextual magnetic field material in class XII students of SMA Negeri 2 Muara Beliti. The research method in this research is Research and Development, while the development model used is ADDIE with 5 stages of Analyze, design, devlopment, implementation and evaluation. The population in this study was class XII IPA 3 with 28 students. The sampling technique used positive sampling using 6 samples. Data collection techniques in this study used interviews, observation, diagnostic test questions, expert validation questionnaires, teacher response questionnaires, student response questionnaires and contextual-based physics textbooks. The results of the validation questionnaire data analysis with 3 validator experts were the results of the validation of the physics lecturer material 42, the results of the validation of the physics teacher material with a score of 46. The results of the validation of the linguists got a score of 18, the results of the validation of the media expert got a score of 35, so the final score obtained after validation of 35 in the very good category, the results of the 6 student response questionnaires obtained a score of 3.7 with the category of strongly agree and the results of the questionnaire response of the teacher and students got a score of 3.6 with the category of strongly agree. The results of competency test scores to support practicality obtained competency test scores obtained by an average of 80.3% complete reaching ≥ 75. So it can be said that the Textbook of Physics Based on Contextual Magnetic Field Material in Class XII Students of SMA Negeri 2 Muara Beliti is Valid and Practical .